ADOPTING BUILDING INFORMATION MODELING IN CLAIMS MANAGEMENT IN CONSTRUCTION INDUSTRY - Mijwel Aljumaily H.S.; Al-Zwainy F.M.S.; Chiad Alharishawi S.S.; Ali R.H.; Hayder G. (Institute for Educational Research, 2023)
Claims are one of the most important problems in construction projects that lead to conflicts between key stakeholders in the republic of IRAQ. Perhaps the main reason is the adoption of traditional systems in claims management, so the use of modern technologies in project management such as BIM technology can contribute to reducing these claims. The study aims to briefly shed light on the most important claims problems in Iraq, then this study attempts to address the claims problem through adopting BIM technology in developing a claims management prototype; This study highlighted 29 problems related to claims, and this model was evaluated by a group of experts and proved its efficiency in solving most of these problems. This study concluded that the model studied can contribute to addressing the problems of claims in Iraqi construction projects, and the results concluded for a set of research gaps that, if addressed, this model will become more accurate and comprehensive. 2022 Institut za Istrazivanja. All rights reserved.